Analysis of seventh-grade students’ critical thinking skills in solving narrative problems using linear equation content - Aina Dinda Yuzaefa; Nurina Happy; Irkham Ulil Albab (Universitas Sarjanawiyata Tamansiswa, 2025)
Students are required to think critically when solving math problems related to everyday life. However, many still do not pay enough attention to the importance of critical thinking skills in the education system, and teachers tend to guide students to solve problems correctly rather than express ideas or notions. The purpose of this research is to assess and describe students’ critical thinking skills in solving story problems involving linear equations, reviewed from the student’s initial abilities. The method used in this research is descriptive qualitative. The purposive sampling and snowball sampling techniques were used as methods for subject selection in this study. The research subjects consist of 6 seventh-grade students from SMP Negeri 3 Randudongkal selected based on specific criteria, where students had initial ability scores of 80-90, good communication, and were recommended by the teaching teacher. The triangulation used in this research is source triangulation. Written tests and in-depth interviews were used as data collection techniques in this study. The data analysis stage used was reducing data, presenting data, and deriving a conclusion. The analysis results obtained from the written critical thinking skills test and interviews in the research show a conclusion that students with high initial abilities can apply four out of six FRISCO critical thinking skill indicators, namely the indicators of Focus, Reason, Inference, and Clarity in solving story problems involving one-variable linear equations. However, they require a greater understanding and precision to apply the indicator of Situation and Overview. Most students failed to explain their knowledge during the interview, indicating a gap between their written and verbal critical thinking skills. This research can serve as a reference for further studies related to critical thinking skills and help teachers design lessons that pay more attention to the critical thinking abilities of students.